Thoracotomy for repair of esophageal atresia: not as bad as they want you to think - Laberge, J.-M.; Blair, G. K. (Diseases of the esophagus, 2013)
Summary Is it outdated now to do a thoracotomy to repair esophageal atresia (EA)? Our practices and the literature on the subject of thoracoscopic and open thoracotomy repair of EA were reviewed, seeking answers to the following questions: Is it correct to compare the new thoracoscopic approach for the repair of EA against the thoracotomy techniques of 15–30 years ago? Should post‐thoracotomy scoliosis/thoracic deformity reported in up to 56% of patients be a significant current concern? Are the clips used to close the fistula in thoracoscopic repairs as safe as open suture closures? Is the leak and stricture rate similar with thoracoscopic surgery? Are the anesthesia, period of ventilation, pain, time to first feeding, and the length of hospital stay significantly different with current thoracotomy techniques compared with thoracoscopic methods? Is the cosmetic result of a thoracoscopic repair significantly better? Is the learning curve for EA thoracoscopic repair harming patients for minimal long‐term benefit? These questions were scientifically unanswerable at this time. The limited EA thoracotomies currently performed have a track record of proven safety and minimal morbidity. The results published by surgeons who are pioneers in thoracoscopy may not be generalizable, and the complication rate from teams with less experience is likely underreported. In selected patients and with experienced teams, thoracoscopic EA repair is appropriate. However, EA repair via thoracotomy should, for now, remain as the ‘gold standard’. Further registry‐based, multicenter, comparative studies on EA repair methodologies and outcomes should provide important answers.